Growth hormone inhibits the JAK/STAT3 pathway by regulating SOCS1 in endometrial cells in vitro: a clue to enhance endometrial receptivity in recurrent implantation failure - Haixia Li; Ning Sun; Yaqiao Zhu; Wei Wang; Meihong Cai; Xiaohuan Luo; Wei Xia; Song Quan (European Journal of Histochemistry, 2022)
Recurrent implantation failure (RIF) is defined as failure to achieve clinical pregnancy after at least 3 transfers of good-quality embryos by natural or artificial means. RIF is often a complex problem with a wide variety of etiologies and mechanisms as well as treatment options. In this study, using immunohistochemistry and Western blot, we demonstrated that the expression of leukemia inhibitory factor (LIF), Janus kinase 1 (JAK1), and signal transducer and activator of transcription 3 (STAT3) was increased, while that of suppressor of cytokine signaling 1 (SOCS1) was decreased in RIF patients. Growth hormone (GH) administration proved to have positive effects on embryo implantation in RIF patients, but the action mechanism of GH has not been elucidated yet. To this aim, we studied the effects of GH on the proliferation in vitro of endometrial adenocarcinoma Ishikawa cells. GH stimulated the expression of LIF and SOCS1, and through SOCS1 inhibits the expression of phosphorylated STAT3, and finally inhibits the occurrence of RIF. Excessive phosphorylation of STAT can lead to decreased endometrial receptivity and abnormal embryo implantation. We also examined the effects of LIF overexpression and an LIF inhibitor (EC330) on the JAK/STAT pathway. LIF promoted cell proliferation, and the up-regulation of LIF increased the expression of SOCS1 and JAK1/STAT3 pathway-related genes in Ishikawa cells. As GH can inhibit the JAK1/STAT3 pathway through LIF, we hypothesize that upregulating SOCS1 may be a potential approach to treat RIF at the molecular level. GH can inhibit the JAK1/STAT3 pathway through LIF, up-regulating SOCS1 to treat RIF at the molecular level.